Sistem Pendeteksi Plagiarisme untuk Tugas Akhir Mahasiswa di Universitas Bina Nusantara: Studi Pendahuluan - Ernawati, Endang; Anindito, Anindito; Atmojo, Robertus Nugroho Perwiro (Humaniora, 2014)
Article functioned as a preliminary study for the research on plagiarism happened in student’s thesis S1 in Bina Nusantara University and how to overcome this cases by a prevention procedure approved by the students, lecturers, departments, and other supporting units. The preliminary study was done by library research, finding some plagiarism cases, model, the way to prevent the case, and the sanction and punishment related to plagiarism. Results of this library research used for compiling questionnaire that will be contributed to students, thesis advisors, thesis judges, and the departments to get the real condition of plagiarism practices, prevention actions, and some input to support the next research.